Combining Genetic Variants to Improve Risk Prediction for NAFLD and Its Progression to Cirrhosis: A Proof of Concept Study - Umberto Vespasiani-Gentilucci; Chiara Dell’Unto; Antonio De Vincentis; Andrea Baiocchini; Marco Delle Monache; Roberto Cecere; Adriano Maria Pellicelli; Valerio Giannelli; Simone Carotti; Giovanni Galati; Paolo Gallo; Francesco Valentini; et al. (Canadian Journal of Gastroenterology and Hepatology)
Background & Aims. Identifying NAFLD patients at risk of progression is crucial to orient medical care and resources. We aimed to verify if the effects determined by different single nucleotide polymorphisms (SNPs) could add up to multiply the risk of NAFLD and NASH-cirrhosis. Methods. Three study populations, that is, patients diagnosed with NASH-cirrhosis or with noncirrhotic NAFLD and healthy controls, were enrolled. PNPLA3 rs738409, TM6SF2 rs58542926, KLF6 rs3750861, SOD2 rs4880, and LPIN1 rs13412852 were genotyped. Results. One hundred and seven NASH-cirrhotics, 93 noncirrhotic NAFLD, and 90 controls were enrolled. At least one difference in allele frequency between groups was significant, or nearly significant, for the PNPLA3, TM6SF2, and KLF6 variants (p<0.001, p<0.05, and p=0.06, resp.), and a risk score based on these SNPs was generated. No differences were observed for SOD2 and LPIN1 SNPs. When compared to a score of 0, a score of 1-2 quadrupled, and a score of 3-4 increased 20-fold the risk of noncirrhotic NAFLD; a score of 3-4 quadrupled the risk of NASH-cirrhosis. Conclusions. The effects determined by disease-associated variants at different loci can add up to multiply the risk of NAFLD and NASH-cirrhosis. Combining different disease-associated variants may represent the way for genetics to keep strength in NAFLD diagnostics.